Short-term effect of macular edema on the peripapillary retinal nerve fiber layer in patients with wet age-related macular degeneration and diabetic macular edema: A comparative study - Dikmetas, Ozlem; Gungor, Gulce; Kapucu, Yasemin; Kocabeyoglu, Sibel; Kadayıfcılar, Sibel; Eldem, Bora; Karahan, Sevilay; Cankaya, Ali Bülent (Photodiagnosis and photodynamic therapy, 2023)
•Temporal and inferotemporal retinal nerve fiber layer (RNFL) changes appeared to correlate with a decrease in central macular thickness (CMT).•A decrease in RNFL thickness is possible, especially in diabetic macular edema (DME) patients after one intravitreal anti-VEGF injection.•Macular edema treatment with one intravitreal anti-VEGF injection contributes to RNFL changes in the setting of macular edema.•In patients with glaucoma and DME receiving anti-VEGF treatment, it would be prudent to interpret peripapillary RNFL thickness measurements carefully. The combined presence of glaucoma and age-related macular degeneration (ARMD), or glaucoma and diabetes mellitus (DM), occur fairly frequently, especially in elderly patients. This study was intended to compare the effect of resolving macular edema due to DM and wet ARMD on peripapillary retinal nerve fiber layer (RNFL) thickness. This cross-sectional study included 76 patients with macular edema secondary to DM (n = 40, 52.6%) or wet ARMD (n = 36, 47.4%). The control group was comprised of 34 age and sex-matched healthy subjects. All study participants underwent evaluation of central macular thickness (CMT) and the peripapillary RNFL using spectral domain-optical coherence tomography (SD-OCT). Data from eyes that received an anti-VEGF injection were obtained one month after the procedure and were compared with pre-injection data. The average initial thickness of the global peripapillary RNFL was 98.9 ± 16.7 (61–163) µm in the macular edema group and 92.0 ± 16.0 (84–115) µm in the control group (p = 0.045). The post-injection global peripapillary RNFL thickness was 97.3 ± 19.0 (61–163) µm in the macular edema group and 92.2 ± 18.0 (81–126) µm in the control group (p = 0.187). In the DM group, the changes in global RNFL thickness, as well as central and temporal quadrant thicknesses, were found to correlate significantly with the change in CMT (r = 0.356, p = 0.024; r = 0.545, p < 0.001, respectively). Macular edema in wet ARMD appeared not to affect RNFL thickness. Differences in the etiology of macular edema can have varied effects on peripapillary RNFL. It is recommended that peripapillary RNFL thickness be evaluated cautiously in DM patients receiving intravitreal anti-VEGF therapy.